The Characteristics of Patients Associated With High Caregiver Burden in Parkinson's Disease in Singapore - Tan, Mark M. J.; Lim, Ee Chien; Nadkarni, Nivedita Vikas; Lye, Weng Kit; Tan, Eng King; Prakash, Kumar M. (Frontiers in Neurology, 2019)
Introduction: Given the complex multitude of Parkinson’s disease (PD) symptoms, caregiving for PD patients can be highly demanding. Our study was aimed to investigate the characteristics of PD patients related to different levels of caregiver burden. Methods: This cross-sectional study recruited 104 idiopathic PD patient-caregiver pairs. Patients were evaluated on motor, non-motor symptoms and quality of life (QoL). Caregiver burden was quantified using Zarit Burden Inventory and subsequently stratified into 3 subgroups. Statistical analysis was performed to identify differences in the no-or little, mild-moderate and high caregiver burden subgroups. Results: The mean disease duration was significantly longer in the high caregiver burden group compared to no-or little group (9.63 versus 5.17 years; p-value 0.003). The mean levodopa equivalent daily dose (LEDD) and mean total UPDRS Part IV scores (UPDRS4) were significantly higher in the high caregiver burden group compared to no-or little group (p-value 0.011 and 0.004, respectively). The high caregiver burden group had significantly higher median QoL scores (PDQ-39) for PD patients for domain 2 (ADL, p-value 0.005), domain 4 (stigma, p-value 0.005) and domain 6 (cognition, p-value 0.002) compared to no-or little group. Conclusion: Greater caregiver burden was observed in PD patients with more prolonged disease duration, higher LEDD to control motor symptoms as well as greater levodopa related motor complications. Further studies on potential interventions to mitigate or delay levodopa related motor complications may reduce caregiver burden. Marked worsening in patient’s QoL, specifically ADL, stigma and cognition in the high compared to no-or little caregiver burden group suggests the possible utility of monitoring these factors for early indentification of increasing caregiver stress and burden.